The effect between static stretch and pre event massage on kicking speed score among university taekwondo athletes / Mohamad Nizam Mohamed Shapie and Intan Nur Marliana Khiri - Mohamed Shapie, Mohamad Nizam; Khiri, Intan Nur Marliana (Faculty of Sports Science and Recreation, 2016)
This study has been conducted to identify the effect of different athlete’s preparation methods between static stretching and pre-event massage on kicking speed score among taekwondo athletes. Forty-five taekwondo athletes aged between 21 to 26 years old were selected to participate in this study. Subjects were divided into control group (N=15), static stretching (N=15) and pre-event massage group (N=15). All groups followed a supervised 10 seconds kicking speed test in the pre-test and post-test. Paired t-test was utilized to determine the significance at a 95% confidence level (p=0.05) of kicking speed score between the three groups. The control (p-value = 0.499) and static stretching groups (p-value = 0.458) showed no improvement compared to pre-event massage group (p-value = 0.001) that showed changes in the kicking speed number. This study found that pre-event massage intervention was more efficient in assisting speed of kicking to enhance performance compare to static stretching group.